Screening, Identifying of Penicillium K-P Strain and Its Cellulase Producing Conditions - Palani*, N. Karthikeyan, M. Sakthivel and P. (Journal of Ecobiotechnology, 2011)
<span style="font-size: 10pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-fareast-font-family: SimSun; mso-bidi-font-family: Tahoma; mso-ansi-language: EN-US; mso-fareast-language: EN-IN; mso-bidi-language: AR-SA;">Cellulase production by Penicillium species are of greater interest in microbial enzyme technology. Penicillium sp. <span style="font-size: 10pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-fareast-font-family: SimSun; mso-bidi-font-family: Tahoma; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">was cultivated in liquid culture medium at different carbon sources, nitrogen sources in different pH and temperature conditions. The strain of K-P with high cellulase activity was screened. The cellulase activity was 198 U/mL in the presence of fructose on day fifth. Maximum activity was recorded 154 U/mL in with the presence of ammonium nitrate on the fourth day. And maximum cellulase activity was obtained when the pH was 3.0 (129 U/mL) on day fourth. But the highest cellulase activity recorded (274 U/mL) in the presence of fructose, ammonium nitrate, pH 3.0 on the fifth day. The results showed the profiles of cellulase were produced maximum level according to which enzyme is most active in that particular environment.